Multimodality Imaging of Traditional and Novel Cardiac Devices. (31st May 2015) - Ho, Yoona; Brouha, Sharon S.
<x xml:space="preserve">Abstract</x> Traditional and novel cardiac devices are visualized commonly on routine imaging, such as chest radiography and CT. An awareness of the normal and abnormal imaging appearance of such devices is essential for radiologists interpreting routine thoracic imaging studies. This article reviews the imaging appearance of traditional and novel cardiac devices, indications for placement, mode of placement, and potential complications. In addition, we discuss valvular prostheses including those placed via minimally invasive methods, cardiac conduction devices, left atrial appendage clips, atrial septal occluding devices, ventricular assist devices, and total artificial hearts.